Polityka informacyjna parafii diecezji rzeszowskiej – raport z badań - Chmielewski, Zbigniew; Kuca, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
In Roman Catholic Church diocese in Rzeszów in December 2012 and January 2013 research was conducted, the main purpose of which was to define how information policy among priests and parishioners looks. During the research it was diagnosed what is meant by the definition of information policy between Church and parishioners. The research has also shown what kind of tools are used in order to communicate with parishioners and if these tools are efficient. The report presents the main communication barriers and what makes this communication more difficult as well. There were 81 respondents, who came from 81 different parishes within the diocese.
INFORMATION POLICY OF ROMAN CATHOLIC CHURCH’S PARISHES OF THE DIOCESE IN RZESZÓW – RESEARCH REPORT
Keywords: information policy; Roman Catholic Church diocese in Rzeszów; communication barriers; information policy tools